2021
DOI: 10.7717/peerj.11451
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in dental, oral and craniofacial imaging: a review of recent progress

Abstract: Artificial intelligence has been emerging as an increasingly important aspect of our daily lives and is widely applied in medical science. One major application of artificial intelligence in medical science is medical imaging. As a major component of artificial intelligence, many machine learning models are applied in medical diagnosis and treatment with the advancement of technology and medical imaging facilities. The popularity of convolutional neural network in dental, oral and craniofacial imaging is heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 152 publications
0
32
0
Order By: Relevance
“…Of the 7 included systematic reviews [7,[18][19][20][21][22][23], 4 were conducted in Asia (i.e., 2 each from China and India) [18,19,21,22] while 2 reviews was conducted in Europe (Finland) [7,23] and one review in the United States [20] (Table 2). The quality appraisal for all the review papers considered in this study indicated that 42.9% showed high quality [7,21,22] while 57.1% showed medium quality [18][19][20]23]. Three of the reviews were conducted in the year 2020 [18][19][20] while four were conducted in the year 2021 [7,[21][22][23].…”
Section: Characteristics Of Relevant Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 7 included systematic reviews [7,[18][19][20][21][22][23], 4 were conducted in Asia (i.e., 2 each from China and India) [18,19,21,22] while 2 reviews was conducted in Europe (Finland) [7,23] and one review in the United States [20] (Table 2). The quality appraisal for all the review papers considered in this study indicated that 42.9% showed high quality [7,21,22] while 57.1% showed medium quality [18][19][20]23]. Three of the reviews were conducted in the year 2020 [18][19][20] while four were conducted in the year 2021 [7,[21][22][23].…”
Section: Characteristics Of Relevant Studiesmentioning
confidence: 99%
“…The processed training set is fed into the network through the convolutional layer. This layer automatically performs the image feature extraction to produce a feature map [21,22,[52][53][54][55]. However, the produced feature map is still large and needs to be downsized [21].…”
Section: Pipeline For Building a Deep Learning-based Prognostic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrieved feature information must now be fed into the modelling process. On the basis of the feedback from the results, fall-back processes such as hyperparameter adjustment and model adjustment are carried out [15]. The fundamental machine learning technique is shown in Fig.…”
Section: Learning In Image Processingmentioning
confidence: 99%
“…AI applications are commonplace in digital everyday life, for example in the form of virtual assistants such as “Siri” or “Alexa” [ 1 , 4 ], and AI applications are implemented in various engineering fields [ 5 , 6 , 7 ]. In medicine, AI algorithms are ubiquitously used for image processing via feature extraction of specific images and target conducting [ 8 ]. For example, AI algorithms can be used for analyzation of chest X-ray and lung CT image samples images of COVID-19 patients and thus decrease the picture diagnostic time of the radiologist and accelerate clinical decisions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%